2002
DOI: 10.2307/3079268
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology and Genetics of a Host Shift: Microbotryum as a Model System

Abstract: The need to prevent and cure emerging diseases often precludes their continuing study in situ. We present studies on the process of disease emergence by host shifts using the model system of anther-smut disease (Microbotryum violaceum) on the plant genus Silene (Caryophyllaceae). This system has little direct social impact, and it is readily amenable to experimental manipulation. Our microevolutionary studies have focused on the host shift of Microbotryum from Silene alba (=latifolia; white campion) onto Silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
110
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(120 citation statements)
references
References 0 publications
8
110
2
Order By: Relevance
“…The range of parasites that are associated with a particular host species may be influenced by evolution and is primarily influenced by the acquisition and loss of parasite species over time. A host species acquires a parasitic species either by inheritance from ancestral host species (Brooks, 1988) or by exchange with other related or unrelated host species that co-occur in the same geographical area (Antonovics et al 2002;Brooks et al 2006). In contrast, the loss of an associated parasite species can occur through historical 'accidents' (e.g., the abrupt division of a host population in which a founding population becomes isolated and free of a specific parasite species) or by the dispersal of the host species to new environments, which present unfavourable conditions for some parasite species (e.g., the absence of an appropriate intermediate host in the new environment) (Hafner and Page, 1995;Paterson et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The range of parasites that are associated with a particular host species may be influenced by evolution and is primarily influenced by the acquisition and loss of parasite species over time. A host species acquires a parasitic species either by inheritance from ancestral host species (Brooks, 1988) or by exchange with other related or unrelated host species that co-occur in the same geographical area (Antonovics et al 2002;Brooks et al 2006). In contrast, the loss of an associated parasite species can occur through historical 'accidents' (e.g., the abrupt division of a host population in which a founding population becomes isolated and free of a specific parasite species) or by the dispersal of the host species to new environments, which present unfavourable conditions for some parasite species (e.g., the absence of an appropriate intermediate host in the new environment) (Hafner and Page, 1995;Paterson et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cryptococcus neoformans; Goodwin & Poulter, 2001), and how completely an organism must restrict outcrossing to decrease repetitive element diversity is unknown. Here, I describe repetitive DNA in the genome of Microbotryum violaceum, a highly selfing basidiomycete fungus (Antonovics, Hood & Partain, 2002;Garber & Ruddat, 2002;. The study is based on a genome sampling approach that could also be used to investigate the nuclear content in other organisms where complete genome sequencing is not feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, research on disease in natural systems can solidify important research questions and approaches that have practical benefit. Antonovics et al (13), for example, illustrated how studies of fungal infection of a roadside weed allowed them to explore fundamental questions about emerging diseases that would be impossible to address in human or agricultural situations.…”
Section: Future Directionsmentioning
confidence: 99%
“…In two different studies where the anther-smut pathogen was found to infect previously unknown hosts, disease symptoms on the new host were atypical, suggesting poor adaptation (13,76). Inoculation experiments with the new host revealed considerable variation in susceptibility, suggesting the potential for rapid evolution of host resistance (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation